Water chemistry of nuclear reactor systems 8. (British Nuclear Energy Society, 2001)
These conference proceedings address the continuing worldwide interest in the chemistry that determines the operational behaviour of nuclear power stations. This collection of international papers aims to discuss the chemical factors important to the operation of the water circuits of power reactors with minimum corrosion, operator radiation dose and effluent/radwaste discharges.